Robust optimization approach for synthesis of integrated biorefineries with supply and demand uncertainties - Tay, Douglas H. S. (Animo Repository, 2013)
This work presents a robust optimization approach for the synthesis of integrated biorefineries that deals with uncertainties in raw material supply and product demand. This approach makes use of a single-step mixed integer nonlinear programming formulation, which is generated and solved with data from multiple biomass supply and product demand scenarios. Based on the optimized result, detailed allocation of biomass, intermediates, and final products can be determined. The optimal capacity of each process technology can also be found. An illustrative case study is then used to demonstrate the effectiveness of the robust optimization approach to determine the optimum integrated biorefinery configuration and capacity with consideration of uncertainties. © 2012 American Institute of Chemical Engineers.